1985
DOI: 10.1007/bf01541656
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer bias in erotica research: Effects of intrusiveness of measure and sexual background

Abstract: Volunteer characteristics and volunteer rates across several laboratory experiments of sexual arousal were compared. Conditions were created to assess which component of the experimental setting was responsible for low volunteer rates in experiments using genital measurement. Subjects were 324 male and 424 female undergraduate students who had volunteered for an experiment on sexuality and personality. After completing several measures of sexual experience and attitude, subjects received a written description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 20 publications
3
61
0
1
Order By: Relevance
“…There is a selection bias in sexual psychophysiology research, such that individuals who volunteer to participate in sexual psychophysiology experiments are typically more sexually experienced, less concerned about their performance, and have been exposed to more erotica than individuals who do not volunteer to participate (Wolchik, Braver, & Jensen, 1985). That being said, Chivers, Rieger, Latty, and Bailey (2004) suggested that although volunteers differ from non-volunteers in terms of sexual experience, it does not mean that people who volunteer have significantly different patterns of arousal.…”
Section: Discussionmentioning
confidence: 93%
“…There is a selection bias in sexual psychophysiology research, such that individuals who volunteer to participate in sexual psychophysiology experiments are typically more sexually experienced, less concerned about their performance, and have been exposed to more erotica than individuals who do not volunteer to participate (Wolchik, Braver, & Jensen, 1985). That being said, Chivers, Rieger, Latty, and Bailey (2004) suggested that although volunteers differ from non-volunteers in terms of sexual experience, it does not mean that people who volunteer have significantly different patterns of arousal.…”
Section: Discussionmentioning
confidence: 93%
“…First, participants consisted of volunteers who chose to participate in a study on sexuality. Volunteer bias has been demonstrated in studies involving sexuality (Wolchik, Braver, & Jensen, 1985) and, as such, the generalizability of these results is unknown. Second, because of the relatively small sample in the two groups, the proposed sub-types of FSAD could not be examined.…”
Section: Discussionmentioning
confidence: 94%
“…As with all sexual psychophysiology research, the generalizability of laboratory findings is a concern (Morokoff, 1986;Wolchik, Braver, & Jensen, 1985). The consistency with which women's nonspecific genital response, and low agreement with genital response, has been obtained across stimulus modality and measurement methods, however, mitigates these concerns and suggests nonspecificity of heterosexual women's genital arousal is not epiphenomenal or artifactual.…”
Section: Limitationsmentioning
confidence: 89%